SUPPLIER SELECTION AND EVALUATION IN PAPER SUPPLY CHAIN - Nailul Abror, Marimin dan Indah Yuliasih (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACTMore competitive environment, selective raw materials acquisition, its complexity and dynamics have encouraged the actors of paper supply chain to pay more attention in all their functions, including supplier selection and evaluation. The selection of  right suppliers is the first strategic decision determining the success in implementation of supply chain management. This research aimed  to analyze the configuration of paper supply chain (PSC), and to develop a model for the supplier selection and evaluation in the PSC with Analytical Hierarchy Process (AHP) approach. The configuration of PSC was analyzed through its four elements of structures, business processes, resources, and management. To give more detailed description, a case study in PT Kertas Leces (PTKL), a second oldest integrated paper mill in Indonesia, was undertaken. . In this case, PTKL played  as an intermediary manufacturer that produces paper in parent rolls, and then delivered  them to the  costumers, mostly of other manufacturers, as converters and distributors. All processes in customer order cycle and manufacturing cycle were  executed in response to a customer order (pull processes), whereas in procurement cycle were  performed in anticipation of production demand (push processes). Proposed AHP model consisted  of five levels of hierarchies, i.e. goal, criteria, sub-criteria, rating scales, and alternatives. Nineteen subcriteria grouped into four criteria were identified. Its application on a specific supplier selection of recovered paper resulted in cost as the most important criteria, followed by the quality, delivery, and service and management of organization. The use of proposed AHP model indicates that it can be applied to improve the decision-making in supplier selection with a set of systematic and comprehensive analysis.Keywords: paper supply chain, supplier selection, AHP